Problematika Pembuktian Hak Milik Atas Tanah Di Desa Linamnutu, Kecamatan Amanuban Selatan, Kabupaten Timor Tengah Selatan - Mericiana Yulita Fin Tae; Benediktus Peter Lay; Ernesta Uba Wohon (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
. Land rights are rights that are obtained from a legal relationship between the right holder and the land, including space above the ground and or space under the ground. The understanding of land rights is one of the individual rights to land, namely rights that give authority to the holders of the rights, whether individually or also as a group of people collectively or as a legal entity, to use in the sense of controlling, using and or taking advantage of certain land parcels. Ownership of land must have legal certainty, both customary law and land law or positive law concerning the certainty of land rights as property rights so as not to cause conflict. The method used by the author in collecting data is through surveys, interviews and studies of primary literature (books that talk about soil) and secondary literature (supporting books). Survey is a quantitative research using the same structured questions for everyone, then all the answers obtained by the researcher are recorded, processed, and analyzed.